ANTIMICROBIAL EFFECT OF OZONIZED PHYSIOLOGICAL SOLUTION ON BACTERIA CAUSING CYSTITIS IN DOGS - Jaguezeski, Antonise Mariely; Engelmann, Ana Martiele; Seeger, Marlane Geribone; Bueno, Andressa; Cargnelutti, Juliana Felipetto; de Andrade, Cinthia Melazzo (Archives of Veterinary Science, 2024)
Bacterial cystitis is a common clinical problem among dogs and is one of the reasons for the empirically administration of antimicrobials. This practice facilitates the selection of bacteria that are multidrug-resistant to antibiotics. In this context, it is urgent to understand and validate therapeutic modalities that complement antimicrobial treatment in cystitis cases. Ozone therapy has been proposed by scientists both in human and animal medicine. Thus, the objective of this study was evaluated the in vitro antimicrobial activity of ozonized saline solution over standard strains and resistant or multi-drug resistant isolates commonly associated with cystitis in dogs. The plating method was used to evaluate the antimicrobial activity of the exposure of 1 mL of phosphate buffer solution containing 108 colony forming units (CFU) mL-1 for 60 s to 4 mL of ozonized saline solution at 78 µg mL-1 over the standard strains (Staphylococcus aureus and Escherichia coli) and resistant or multi-resistant isolates (Proteus mirabillis, Klebsiella sp. e Enterococcus sp.), and the broth microdilution test to determine the minimum inhibitory and bactericidal concentration for S. aureus, E. coli and Pseudomonas aeruginosa strains from the same solution. The plating was the only assay in which treatment with ozonized saline resulted in bactericidal activity, promoting a reduction of more than 99% of colony-forming units for most of the tested strains, except for P. mirabillis. These results are promising, as these disease is the most common lower urinary tract disorder in dogs, with limited allopathic therapy due to increased bacterial resistance.